Tradition und Moderne im innerjapanischen Tourismus - Schöller, Peter (ERDKUNDE, 1980)
An enquiry into spatially related forms and processes of social life in which Japan has shaped, maintained and further developed its own and specific features, will have to consider leisure activities, recreational traffic and tourism as a significant, increasingly important factor in it. On the one hand intensive commercialisation of mass tourism engaged in a competitive struggle with large Kanko companies increasingly leads to the destruction of landscapes, the endangering of the environment and to over-development of leisure facilities; on the other hand an adaptation of life forms takes place within the rapidly expanding inland tourism. Age groups and macro-regional differentiations become more important than specific class differences in attitudes to travel and leisure. Another social leveller is the continuing dominance of short journeys, which combine experience, change and mass organisation with education and community feeling. The increase in motorisation and the opening up of new destinations for nature, high altitude and sport-based tourism promote the transition to -albeit still brief-family-related recreational holidays. Inspite of these tendencies specific features of traditional Japanese social attitudes remain alive in the principle of group travel and in the concentration on traditional destinations for visits to places such as spas with hot springs (Onsen), temples, shrines and famous viewpoints. Even in the modern forms of landscape and urban tourism and in the attractions of tourist pleasure life or socially obligating and value-related traditions remain alive. The openness to traditional landscape impressions, the will to be educated, and the identification and ability to be impressed continue to be determing elements, which link this modern society with its historical past.